Ocular safety of repeated intravitreal injections of Carboplatin and Digoxin: A preclinical study on the healthy rabbits - Alireza Khodabande; Fariba Ghassemi; Fahimeh Asadi Amoli; Hamid Riazi‐Esfahani; Raziyeh Mahmoudzadeh; Mohammad Mehrpour; Niloufar Valipour (Wiley, 2021)
Abstract To evaluate the ocular safety of intravitreal carboplatin and digoxin injections as a new intravitreal chemotherapy option for retinoblastoma tumor vitreous seeds. Eighteen rabbits were divided randomly into three groups to receive intravitreal injection of Digoxin (6 rabbits), Carboplatin (7 rabbits), or Saline (5 rabbits). In every group, one eye randomly treated with 10 µg Digoxin in 0.1 cc or 1 µg Carboplatin or Saline, and the contralateral eye was considered as the control. All groups underwent three consecutive injections of the drugs with 1‐week intervals. Baseline electroretinography (ERG) was recorded from both eyes of all the animals prior to injection and was repeated 1st day, 1st week, and 1st month after the last injection. All rabbits were sacrificed 1 month after the last injection, and histological studies were done. Mean a and b wave amplitudes decreased significantly at 1st day, 1st week, and 1st month after the last intravitreal injection of 10 µg Digoxin in comparison with other groups (p‐value: .02). Contradictory, 1 µg Carboplatin injected eyes had minimal ERG changes. There were some nonspecific ERG changes with unclear clinical significance in non‐injected contralateral control eyes of Digoxin and Carboplatin groups in comparison with the control eyes of the Saline group. Histological studies revealed considerable neural retinal atrophy in injected eyes of the Digoxin group. Intravitreal 10 µg Digoxin might have more local ocular toxicity in comparison with intravitreal Carboplatin in albino rabbit eyes. Future studies should assess the induced toxicity of intravitreal injection of these drugs on the non‐injected contralateral eye.